Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1681/asn.2012010022
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Liver X Receptor Inhibits Osteopontin and Ameliorates Diabetic Nephropathy

Abstract: Osteopontin is a proinflammatory cytokine and monocyte chemoattractant implicated in the pathogenesis of diabetic nephropathy. Synthetic agonists for liver X receptors (LXRs) suppress the expression of proinflammatory genes, including osteopontin, but whether LXR activation modulates diabetic nephropathy is unknown. We administered the LXR agonist T0901317 to mice with streptozotocin-induced diabetes and evaluated its effects on diabetic nephropathy. The LXR agonist decreased urinary albumin excretion without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 55 publications
6
42
0
Order By: Relevance
“…As described above, treatment with statins and antihypertensive agents has previously been shown to influence osteopontin activity [22]. Remarkably, studies done in mice showed that inhibition of renal osteopontin by liver X receptor agonists may have a therapeutic value for diabetic nephropathy [26], and several other preclinical animal studies using loss-of-function approaches have demonstrated osteopontin as a therapeutic target [27]. Whether the measurement of plasma or urinary osteopontin will be useful in guiding the initiation and monitoring of osteopontin-modulating treatments remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, treatment with statins and antihypertensive agents has previously been shown to influence osteopontin activity [22]. Remarkably, studies done in mice showed that inhibition of renal osteopontin by liver X receptor agonists may have a therapeutic value for diabetic nephropathy [26], and several other preclinical animal studies using loss-of-function approaches have demonstrated osteopontin as a therapeutic target [27]. Whether the measurement of plasma or urinary osteopontin will be useful in guiding the initiation and monitoring of osteopontin-modulating treatments remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…This new model of renal disease may be relevant to human disease, since the expression of LXRα and LXRβ is significantly decreased in patients with DN compared with controls [27] and renal biopsies from patients with DN show lipid deposition primarily in glomeruli [41][42][43]. Recent studies looking at LXR action in the kidney have shown improved albuminuria with other LXR ligands (T091317, GW3965) and different animal models of DN (STZ C57Bl/6, STZ Ldlr −/− ) [28,29]; however, these studies were unable to address the importance of LXR in baseline renal function. The authors attributed the improvement in renal function to inhibition of the proinflammatory gene osteopontin in renal tubular cells [29] or to enhanced activity of macrophage LXRα [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies looking at LXR action in the kidney have shown improved albuminuria with other LXR ligands (T091317, GW3965) and different animal models of DN (STZ C57Bl/6, STZ Ldlr −/− ) [28,29]; however, these studies were unable to address the importance of LXR in baseline renal function. The authors attributed the improvement in renal function to inhibition of the proinflammatory gene osteopontin in renal tubular cells [29] or to enhanced activity of macrophage LXRα [28]. In contrast, our data, supported by loss of function and gain of function (using a gene-selective LXR ligand), suggest a more complex mechanism, which includes protection from lipid deposition in the glomerulus and inhibition of renal inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glomerular fi ltration rate (eGFR) was estimated using the CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) formula ( 29,30 ). Twentyfour hour urine albumin, protein, and creatinine were available to all patients in the last month prior to biopsy.…”
mentioning
confidence: 99%